Isoniazid acetylating phenotype in patients with paracoccidioidomycosis and its relationship with serum sulfadoxin levels, glucose-6-phosphate dehydrogenase and glutathione reductase activities - Barraviera,Benedito (1991)
The authors evaluated the isoniazid acetylating phenotype and measured hematocrit, hemoglobin, glucose-6-phosphate dehydrogenase and glutathione reductase activities plus serum sulfadoxin levels in 39 patients with paracoccidioidomycosis (33 males and 6 females) aged 17 to 58 years. Twenty one (53.84%) of the patients presented a slow acetylatingphenotype and 18(46.16%) a fast acetylating phenotype. Glucose-6-phosphate- dehydrogenase (G6PD) acti vity was decreased in 5(23.80%) slow acetylators and in 4(22.22%) fast acetylators. Glutathione reductase activity was decreased in 14 (66.66%) slow acetylators and in 12 (66.66%) fast acetylators. Serum levels of free and total sulfadoxin Were higher in slow acetylator (p < 0.02). Analysis of the resultspermitted us to conclude that serum sulfadoxin levels are related to the acetylatorphenotype. Furthermore, sulfadoxin levels were always above 50 µg/ml, a value considered therapeutic. Glutathione reductase deficiency observed in 66% of patients may be related to the intestinal malabsorption of nutrients, among them riboflavin, a FAD precursor vitamin, inpatients with paracoceidioidomycosis.